Factors Influencing Prescribing Perceived Utility of Drugs: Experiences from Iraqi Kurdistan - Deldar Abdulah; Karwan Ali Perot (University of Minnesota Libraries Publishing, 2019)
Introduction: Pharmaceutical expenditures have increased dramatically in most developed and developing countries in recent decades. Healthcare system policymakers have expressed concerns about the inappropriate, irrational, or harmful prescribing of drugs. Objectives: The attitudes of physicians towards prescribing generic drugs and predictors of perceived utility of drugs were investigated in the present study. Methods: In this cross-sectional research, 77 physicians at different levels of job hierarchies, working in various public sector shifts, were recruited to participate in a survey of their attitudes toward prescribing generic drugs in Iraqi Kurdistan in 2018. The doctors were located in a general, an emergency, and a pediatric hospital. A self-administered structured questionnaire was designed based on the extended technology acceptance model for product use (TETPU). Results: The doctors agreed that drugs should be prescribed according to their utility for patients (median [M] = 5.0; interquartile range [IQR] = 2.9). Most of the physicians mentioned that they prescribed drugs according to the patients' needs (75.0%), evaluation of the availability of alternatives (69.0%) and consumer perceptions of a price (69.0%). The analysis showed that (1) the importance of physicians' perceptions and their recognition of patients' need achievement (P=.012), (2) the physicians' recognition of the actual use of drugs by consumers (P=.030) and (3) being male (p=.009) were associated with perceptions of drug utility. Conclusions: The study's results suggest that perceived drug utility in prescription writing is associated with physicians' perceptions of need achievement and attitudes toward how patients actually use medicines.   Article Type: Original Research